Get sleep or get stumped: sleep behaviour in elite South African cricket players during competition - McEwan, Kayla (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Introduction: Good sleep behaviour is associated with achieving optimal athletic performance and reducing the risk of injury. Elite cricket players have unique physical and cognitive demands, and must accommodate for congested competition and travel schedules (all of which increase the risk of disruptive sleep). Further, the political pressures and socioeconomic barriers in South African cricket could affect the sleep of the country's elite players. Previous research in cricket has focussed on the impact that nutrition, equipment specifications, movement physiology and psychology could elicit on performance (where many professional teams hire support staff to supervise these disciplines); however, there is limited empirical application of sleep research in elite cricket players. Therefore, this study aimed to characterise the sleep behaviours of elite South African cricket players during periods of competition and investigate the relationship between pre-match sleep and cricket performance. Methods: A longitudinal field-based investigation was implemented to monitor the sleep behaviour of 26 elite South African cricket players (age: 28.6 ± 4.0 years; height: 1.8 ± 0.1 m; weight: 85.7 ± 10.8 kg; elite experience: 3.7 ± 4.0 years) during home and away competitive tours. The Morningness-Eveningness Questionnaire and Athlete Sleep Behaviour Questionnaire were administered to identify chronotype and poor sleep behaviours. Players completed an altered version of the Core Consensus Sleep Diary every morning post-travel, pre-match and post-match. Linear mixed model regression was used to compare differences in sleep variables between time-periods, match venues, player roles, match formats, sleep medication and racial groups. Spearman's correlation (rs) was used to assess the relationship of substance use (alcohol and caffeine), age, elite experience and match performance with selected sleep indices. Statistical significance for all measures was accepted at p < 0.05. Hedge's (g) were used as the measure of effect size. Results: Light-emitting technology use, effects of travel, late evening alcohol consumption and muscle soreness were the main factors that impacted sleep. Post-match total sleep time (06:31 ± 01:09) was significantly (p < 0.05) shorter compared to post-travel (07:53 ± 01:07; g = 1.19 [0.81;1.57]) and pre-match (08:43 ± 01:03; g = 1.97 [1.55;2.39]) total sleep time. Post-travel sleep onset latency and sleep efficiency were significantly (p < 0.05) shorter (g = 0.74 [0.29;1.29]) and higher (g = 1.35 [0.76;1.94]) at home than away. Although not significant (p > 0.05), allrounders took longer to fall asleep (g = 0.90 [0.23;1.57]), obtained less total sleep (0.76 [0.29;1.42]) and had lower morning freshness scores (g = 1.10 [0.42;1.78]) the night before a match compared to batsmen. Wake after sleep onset and get up time were moderately longer (g = 0.61 [0.22;1.26]) and later (g = 0.62 [0.27;1.17]) before. Twenty20 matches compared to One-Day International matches respectively. Further, sleep duration significantly declined from pre-match to post-match during the multi-day Test format (p = 0.04, g= 0.75 [0.40;1.12]). Late alcohol consumption was significantly (p < 0.05) correlated with a decrease in total sleep time, regardless of match venue (home: rs (49) = -0.69; away: rs (27) = -0.57). During the away condition, an increase in age was significantly associated with longer wake after sleep onset durations (rs (13) = 0.52, p = 0.0003), while greater elite experience was significantly associated with longer total sleep time (rs (72) = 0.36, p = 0.02). The non-sleep medication group took significantly longer to fall asleep compared to the sleep medication group during the first week of the away condition (p = 0.02, g = 0.75 [0.25;1.26]) particularly on nights following transmeridian travel. Although not significant ( p > 0.05), Asian/Indian players had moderately longer sleep onset latencies (g = 1.07 [0.66;1.47]), wake after sleep onset durations (g = 0.86 [0.42;1.29]), and lower subjective sleep quality (g = 0.86 [0.46;1.26]) and morning freshness scores (g = 0.89 [0.47;1.27]) compared to Whites. Similarly, Black Africans had moderately lower subjective sleep quality scores compared to Whites (g = 0.71 [0.43;0.97]). Longer sleep onset latencies and shorter total sleep times were significantly (p < 0.05) associated with poorer One-Day International (rs (28) = -0.57) and Test (rs (12) = 0.59) batting performances respectively. Higher subjective sleep quality scores were significantly associated with better Twenty20 bowling economies (rs (8) = -0.52). Discussion: There was no evidence of poor pre-match sleep behaviour, irrespective of venue; however, the most apparent disruption to sleep occurred post-match (similar to that found in other team-sports). Most disparities in sleep between match venues existed post-travel, with better sleep behaviour observed during the home condition. The differences in sleep patterns found in all three match formats were expected given the variations in format scheduling and duration. Although sleep medication was shown to promote better sleep, its long-term effectiveness was limited. The results promote the implementation of practical strategies aimed to reduce bedtime light-emitting technology use, late evening alcohol consumption and muscle pain. Inter-individual sleep behaviour was found between player roles, age, experience level and race. Moderate associations existed between sleep and markers of batting performance, specifically for the longer, strategic formats of the game. Conclusion: The current study provided new insight of the sleep behaviour in elite South African cricket players during competition. Individualized sleep monitoring practices are encouraged, with specific supervision over older, less experienced players as well as the racial minorities and allrounders of the team. The poor post-match sleep behaviour, together with the sleep and performance correlations, provide ideal opportunities for future interventions to focus on match recovery and the use sleep monitoring as a competitive advantage.
Keywords: Sleep -- Physiological aspects; Cricket players -- Health and hygiene; Cricket players -- South Africa -- Health and hygiene; Cricket -- Health aspects